Land use planning by using ArcGIS software: a case study / Mohammad Anas Azmi - Azmi, Mohammad Anas (Faculty of Plantation and Agrotechnology, 2018)
Land used planning is a land where it has been used to develop a vegetative area for the economics and social environment. The purpose of using Precision Agriculture was to give benefit for developing the land used planning efficiently by saving the time and operational cost. The purpose of this study is to design the land used that has been identified for development of double stage nursery consists of pre-nursery and main nursery. ArcGIS Software 10.3 has been used in this procedure. This study was conducted at Jasin, Melaka. There are five different designs mapped in the ArcGIS to show the nursery area for pre-nursery, main nursery, road, drainage, store, hut and engine pump water. Then, using ArcGIS features, each area was calculated to estimate the number of polybag needed for each designed. Each designed was evaluated according to the criteria identified in term of the area involved, road accessibility, security, shaped of sub-block division and drainage and irrigation system. Comparison was made between each of the designs based on the score from the weightage value. The designed with highest score was chosen to be applied in the field. In conclusion, technological advancement such as ArcGIS makes farmer’s lives much easier as it can map their field and monitor the production. Thus, Precision Agriculture can be recommended as a better alternative than the existing traditional method.